What makes a ban on plastic bags effective? The case of Nepal. (11th April 2020) - Bharadwaj, Bishal; Baland, Jean Marie; Nepal, Mani
Abstract: The extensive use of plastic bags in Nepal has led to growing concern in recent years. We investigate the impact of a municipal plastic bags ban on bags use behavior, based on a field survey carried out among consumers and retailers across selected municipalities. Our results indicate that the effectiveness of the ban critically depends on its enforcement and sanctioning system. In particular, our results suggest that the perceived sanction is a critical determinant of plastic bags use, as a doubling of the perceived sanction could reduce plastic bags use by two-thirds for retailers and by one-half for consumers. While the nominal amount of the fine does not seem to play a role, the probability of being detected appears to play a key role in the perceived sanction. This implies that effective monitoring of the ban by the municipal authorities is critical for the success of the policy.